A comparative study on aspects that influence the sense of presence in virtual environments (Revista Brasileira de Computação Aplicada, 2013)
An objective and advantage of Virtual Reality is to promote the sense of “being there”, to be present. Most existing research in this field is focused on determining “if” a given factor contributes to the sense of presence. This paper compares two visualization systems regarding their contribution to the sense of presence, assessing which one contributes the most. Two low-cost low-tech systems were considered: anaglyph-based stereoscopy and large Field-of-View (FOV) screens. The SUS Questionnaire was applied to 63 participants to assess their sense of presence. Participants were divided in two groups on a between-subject experiment and watched a guided tour on a virtual University campus. It was found that both systems contribute to increase presence, but data shows that anaglyph-based stereoscopy contribute more than FOV enlargement. We conclude by suggesting that the very first step to raise the immersion of a Virtual Environment should be using stereoscopy, at least the anaglyph-based one